Management of patients with severe hypertension in emergency department, Maharaj Nakorn Chiang Mai Hospital - Sruamsiri,K. (Medical Association of Thailand, 2015)
© 2014, Medical Association of Thailand. All rights reserved. Background: Management of patients with severe hypertension without progressive target organ damage remains controversial. Some guidelines mentioned oral anti-hypertensive medication as a treatment to reduce blood pressure in the emergency department, while others recommended against such treatment. Objective: To review the management of patients with severe hypertension without progressive target organ damage in the emergency department, Maharaj Nakorn Chiang Mai hospital. Material and Method: In a retrospective descriptive analysis study, medical records of adult patients diagnosed with severe hypertension without progressive target organ damage between January 2011 and December 2012 were reviewed. Patient demographics, data on management including investigation sent and treatment given were collected. Statistical analysis was done by using descriptive statistics and Kruskal-Wallis one-way analysis of variance test. Results: One hundred fifty one medical records were reviewed. Four oral anti-hypertensive medication were used to reduce blood pressure, Amlodipine, Captopril, Hydralazine, and Nifedipine. There were no significant difference between each medication in terms of their effect on blood pressure reduction (p = 0.513). No side effect or other complications from the use of oral anti-hypertensive medication were recorded. Conclusion: The choice of medication used for the treatment of hypertensive urgency ranged from Amlodipine, Captopril, Hydralazine, and Nifedipine, which varied in dosage. However, their efficacies were the same when compared with each other, and none produced any notable side effects.